Night-day speed ratio of elephants as indicator of poaching levels. (January 2018) - Ihwagi, Festus W.; Thouless, Chris; Wang, Tiejun; Skidmore, Andrew K.; Omondi, Patrick; Douglas-Hamilton, Iain
Highlights: Elephants alter their travel speed to avoid encountering poachers. Elephants travel more at night than during the day in areas with higher poaching levels. The night-day speed ratio is an effective metric for measuring the change in movement rate. Application of night-day speed ratio can complement field based monitoring. Abstract: Poaching has escalated in recent years and is becoming the greatest immediate threat to elephants' survival. There is an urgent need to develop innovative and cost-effective methods for monitoring changes in elephant poaching levels remotely to complement the existing traditional field-based ground surveys. Since elephants are known to respond to anthropogenic risks by alterations in their speed of travel, we quantified this alteration as a ratio of night time speed to the day time speed (night-day speed ratio) and examined its relationship with poaching levels. Our hypothesis here is that poaching is a clear daytime risk, and thus an increase in night time movement rates over those seen during the day will support this hypothesis. Using elephant GPS tracking and mortality data collected in the Laikipia-Samburu ecosystem of northern Kenya between 2002 and 2012, we calculated the mean night-day speed ratio for collared elephants that utilised any of 13 contiguous land units, each under different ownership and management status, and related this ratio to the corresponding poaching levels before and during a poaching surge. Our study shows that the mean night-day speed ratio of both male and female elephants did not vary significantly by month, ruling out possible seasonal effect. However, both male and female elephants moved more at night than during the day where and when poaching levels were high. The relationship between poaching levels and night-day speed ratios was stronger for females than for males. We concluded that the variation in the night-day speed ratio of elephants might be used as an effective indicator for changes poaching levels on a near real-time basis. We recommend its adoption as a complimentary anti-poaching tool, where GPS tracking data is already available, because it would increase the geographical range for monitoring of poaching levels. The significant alteration in movement behaviour by elephants in response to poaching also has potential implications for their foraging strategy, reproduction and ultimate survival, all of which are not yet fully understood.